COVID-19 pandemic and arterial hypertension: theoretic-reflexive test in the light of the Model of Care for Chronic Conditions (Research, Society and Development, 2022)
The interest of this essay is oriented towards the production of knowledge in nursing, in order to foster a reflective look, planning and care for people with hypertension. In this sense, the reflections aim to analyze the adequacy of the Care Model for Chronic Conditions during the pandemic in monitoring people with hypertension. This is a theoretical-reflective essay, based on the analysis of scientific articles, considering arterial hypertension, in the light of the Chronic Conditions Care Model. The attention to chronic conditions already faced adversities imposed by the assisted, based on the exacerbation, currently, this adds to the impacts of COVID-19. Among the adversities, there is the difficulty in monitoring, in view of the collapse of the health system, the increase in inequalities and socioeconomic difficulties, reflected in the increase of people with hypertension and difficulty in controlling them. The Model's premises can contribute, since it considers sanitary adaptations, socioeconomic conditions and lifestyle habits. As reflections, they showed that knowledge and implementation of the Model by professionals, especially nursing, is essential to ensure comprehensive care for chronic conditions, such as high blood pressure, especially with the mishaps arising from a pandemic.